Genome-wide detection of Wolbachia in natural Aedes aegypti populations using ddRAD-Seq - Muharromah, Atikah Fitria; Reyes, Jerica Isabel L.; Kagia, Ngure; Watanabe, Kozo (Frontiers in Cellular and Infection Microbiology, 2023)
Background Wolbachia, an endosymbiotic bacterium, is globally used to control arboviruses because of its ability to block arboviral replication and manipulate the reproduction of Wolbachia host, Aedes aegypti. Polymerase chain reaction (PCR)-based Wolbachia detection has been recently reported from natural Ae. aegypti populations. However, due to the technical limitations of PCR, such as primer incompatibility, PCR-based assays are not sufficiently reliable or accurate. In this study, we examined double digestion restriction site-associated DNA sequencing (ddRAD-Seq) efficiency and limitations in Wolbachia detection and quantification in field-collected Ae. aegypti natural populations in Metro Manila, the Philippines, compared with PCR-based assays. Methods A total of 217 individuals Ae. aegypti were collected from Metropolitan Manila, Philippines. We separated it into 14 populations consisting of 7 female and male populations. We constructed a library for pool ddRAD-Seq per population and also screened for Wolbachia by PCR assays using wsp and 16S rRNA. Wolbachia density per population were measured using RPS17 as the housekeeping gene. Results From 146,239,637 sequence reads obtained, 26,299 and 43,778 reads were mapped across the entire Wolbachia genome (with the wAlbA and wAlbB strains, respectively), suggesting that ddRAD-Seq complements PCR assays and supports more reliable Wolbachia detection from a genome-wide perspective. The number of reads mapped to the Wolbachia genome per population positively correlated with the number of Wolbachia-infected individuals per population based on PCR assays and the relative density of Wolbachia in the Ae. aegypti populations based on qPCR, suggesting ddRAD-Seq-based semi-quantification of Wolbachia by ddRAD-Seq. Male Ae. aegypti exhibited more reads mapped to the Wolbachia genome than females, suggesting higher Wolbachia prevalence rates in their case. We detected 150 single nucleotide polymorphism loci across the Wolbachia genome, allowing for more accurate the detection of four strains: wPip, wRi, TRS of Brugia malayi, and wMel. Conclusions Taken together, our results demonstrate the feasibility of ddRAD-Seq-based Wolbachia detection from field-collected Ae. aegypti mosquitoes.